The Guidelines for Promoting Morality and Ethics for Students of Phibunrakpittaya School, Phibunrak District, Udon Thani Province - Samacitto, Phra Thirada; Phra Soponphanabundit; Phramaha Daosayam Vajirapañño (Dhammathas Academic Journal, 2022)
The objectives of this research were: 1) to study the moral and ethical principles in Buddhism; 2) to study the moral and ethical promotion for students of Phibunrakpittaya School, Phibunrak District, Udon Thani Province; 3) to study the guidelines for promoting morality and ethics for students of Phibunrakpittaya School. This study was carried out by means of qualitative research. The obtained data were presented by the descriptive synthesis. The research results were as follows: 1. Buddhist moral and ethical principles could develop students’ minds in order to acquire human qualities which lead to happiness and peaceful coexistence. 2. Promotion of morality and ethics for students of Phibunrakpittaya School can be made by inserting ethics in five areas: generosity, economics, diligence, discipline and honesty in teaching and learning to develop students to have good ethical behaviors along with better academic performance. 3. The guidelines for promoting morality and ethics for students of Phibunrakpittaya School were that the school should place the particular emphasis on the cultivation of morality and ethics by creating self-awareness from insertion in teaching for students to have morals and ethics and to be a good person with knowledge for better social development.